The ideal English pronunciation resource: non-native teachers’ beliefs - Castillo-Rodríguez, Cristina Milagrosa; Torrado Cespón, Milagros; Lago Ferreiro, Alfonso (Universidad del Zulia, 2023)
This paper aimed to explore teachers’ beliefs on the digital resources for an adequate practice of English pronunciation/phonetics. Two teacher samples were collected: preuniversity teachers (secondary education and vocational training) (PU = 51) and university teachers (UN = 76). The results showed that i) PU teachers usually employed paperbased materials from textbooks whilst UN teachers created their own materials; ii) pronunciation practice was integrated into activities devoted to practising speaking and listening skills; iii) teachers would like to employ more materials to download and specialized websites to practice phonetics; and iv) their ideal resource should be ‘reusable’, ‘multimedial’, and ‘open’.
https://produccioncientificaluz.org/index.php/opcion/acceso
Keywords: Lengua inglesa - Estudio y enseñanza; Inglés - Manuales para extranjeros; Investigación activa en educación; English pronunciation; English as a foreign language; Teachers' perceptions; Tools